# Transfer Function from input to node [closed]

From the IIR filter flow graph below i don't understand how the transfer function is calculated in every node:

## closed as off-topic by jojek♦, Matt L., sansuiso, Naresh, Peter K.♦May 8 '14 at 1:25

• This question does not appear to be about signal processing within the scope defined in the help center.
If this question can be reworded to fit the rules in the help center, please edit the question.

• Cross-posted on math.SE. Already answered there. – Matt L. May 29 '13 at 20:33
• Duplicate of: click – jojek Apr 23 '14 at 6:40

There are different ways to do this. Here is an example of the straight forward way. First write down the difference equations and corresponding z-transforms

$p_n^1 = bc_2x_n -a_2y_n \Leftrightarrow P^1(z) = bc_2X(z) - a_2Y(z)$

$y_n = bx_n + p^3_{n-1} \Leftrightarrow Y(z) = bX(z) + z^{-1}P^3(z)$

$p^3_n = p^1_{n-1} + p^2_n \Leftrightarrow P^3(z) = z^{-1}P^1(z) + P^2(z)$

$p^2_n = bc_1x_n - a_1y_n \Leftrightarrow P^2(z) = bc_1X(z) - a_1Y(z)$

Then obtain an expression for $Y(z)$ that only depends on $X(z)$ and $P^1(z)$ $Y(z) = bX(z) + z^{-1}[z^{-1}P^1(z) + P^2(z)]$ $Y(z) = bX(z) + z^{-1}[z^{-1}P^1(z) + bc_1X(z) - a_1Y(z)]$ $Y(z) = bX(z) + z^{-2}P^1(z) + bc_1z^{-1}X(z) - a_1z^{-1}Y(z)$ $Y(z)[1 + a_1z^{-1}] = [b+bc_1z^{-1}]X(z) + z^{-2}P^1(z)$ $Y(z) = \frac{b+bc_1z^{-1}}{1 + a_1z^{-1}}X(z) + \frac{z^{-2}}{1 + a_1z^{-1}}P^1(z)$

Then eliminating $Y(z)$ in the expression for $P^1(z)$

$P^1(z) = bc_2X(z) - a_2Y(z)$ $P^1(z) = bc_2X(z) - a_2[\frac{b+bc_1z^{-1}}{1 + a_1z^{-1}}X(z) + \frac{z^{-2}}{1 + a_1z^{-1}}P^1(z) ]$ $P^1(z)[1+\frac{a_2z^{-2}}{1 + a_1z^{-1}}] = [bc_2 - \frac{a_2(b+bc_1z^{-1})}{1 + a_1z^{-1}}]X(z)$ $P^1(z)[\frac{1 + a_1z^{-1}+a_2z^{-2}}{1 + a_1z^{-1}}] = \frac{bc_2(1 + a_1z^{-1}) -a_2(b+bc_1z^{-1})}{1 + a_1z^{-1}}]X(z)$

$\frac{P^1(z)}{X(z)} = \frac{bc_2(1 + a_1z^{-1}) -a_2(b+bc_1z^{-1})}{1 + a_1z^{-1}+a_2z^{-2}}$ $\frac{P^1(z)}{X(z)} = \frac{bc_2 + bc_2a_1z^{-1} -a_2b-a_2bc_1z^{-1}}{1 + a_1z^{-1}+a_2z^{-2}}$

$\frac{P^1(z)}{X(z)} = b\frac{c_2 -a_2 + (c_2a_1-a_2c_1)z^{-1}}{1 + a_1z^{-1}+a_2z^{-2}}$

Your expression for the transfer function to node 1 is missing the input gain $b$.

Anyway, another way to derive expressions for transfer functions is to use something called Mason's rule. See here wikimason.